Finding New Homes for Dress Collections: The Case Study of the Suddon-Cleaver Collection. (3rd September 2018) - Mida, Ingrid; Kim, Alexandra
Abstract: When private collectors amass collections of significant size, there often comes a point where disposition must be addressed. This article will explore the complex process of finding new homes for dress collections, using the case study of the Suddon-Cleaver collection and linking it to Walter Benjamin's reflections on book collecting in the essay "Unpacking my Library." Although the process of breaking up a collection is associated with negative connotations, this Canadian case study will show how the process can serve to optimize access and value, especially at a time when museum resources are limited and overstretched. Other examples of redistributed dress collections will be reviewed including the dispersal of the wardrobe of Georgian banker Thomas Coutts and the Brooklyn Museum dress collection transfer to the Metropolitan Museum of Art. We argue that the process of finding multiple new homes should be viewed as a way of liberating the best pieces in the collection from the burden of items that are of low value or in poor condition. In carefully articulating the process of distributing the Suddon-Cleaver collection, this article outlines a process that may be adapted for similar dispersals.